Post-pandemic Formative Learnings from COVID-19 Applied to Graduate Programs: Adopting the Blended Learning Model in the Master's Degree in Tropical Apiculture (Revista Electrónica Calidad en la Educación Superior, 2024)
The Master's in Tropical Apiculture (MAT) at the Tropical Beekeeping Research Center (CINAT) of the National University (UNA) focuses on specialized training in apiculture in the Mesoamerican region. Initially offered in a face-to-face format, the program uses practical field and laboratory methods and collaborated with producers and government sectors. Always seeking quality, it was accredited by the Central American Accreditation Agency for Postgraduate Studies (ACAP). The COVID-19 pandemic drives the transition to a blended learning model to facilitate access to students and reduce costs, combining in-person and virtual teaching. This modality leverages technology to personalize learning, promote autonomy, and develop digital skills in a collaborative environment.This article presents a qualitative study that analyzes the formative learnings post-pandemic applied to the MAT. Through a case study that includes interviews and document review, it explores the methodological and technological adaptations implemented during and after the pandemic, focusing on the transition to blended learning models and their impact on the educational quality of the program.
Keywords: Blended learning; Technology-enhanced education; accreditation in graduate programs